Metaphysics of Nepali Society: Analysis from Power and Class Dimension - Nepali, Bishnu Bahadur; Neupane, Bibek Kanta (NPRC Journal of Multidisciplinary Research, 2025)
Background: Nepalese society is characterized by a complex interplay of caste, class, ethnicity, and power dynamics, which have historically shaped social hierarchies and access to resources. The metaphysical foundations of power have perpetuated divisions between dominant and marginalized groups, leading to systemic inequalities. This paper examines the historical and contemporary manifestations of power and class in Nepal, focusing on how societal structures have evolved through political, economic, and social reforms. Objectives: The primary objective of this study is to analyze the transformation of power relations in Nepali society from a historical perspective to the present, with a focus on marginalized communities. It seeks to evaluate how affirmative policies and constitutional provisions have addressed caste and class disparities, promoting social inclusion and equity. Methods: This research employs a qualitative and interpretive methodology, drawing on critical theory and thematic content analysis. Secondary sources, including peer-reviewed articles, policy documents, and historical texts, were reviewed to assess the metaphysical underpinnings of power and class in Nepal. Marxist and post-structuralist frameworks were used to contextualize the findings. Findings: The study reveals that while historical power structures—such as the Rana regime and feudal systems—reinforced caste and class hierarchies, recent policy interventions have initiated transformative changes. Decentralization, constitutional reforms, and affirmative action policies have gradually empowered marginalized groups. However, residual inequalities persist due to deep-rooted socio-cultural norms and uneven policy implementation. Conclusion: Nepali society is undergoing a significant shift toward inclusivity, driven by legal reforms and social movements. While progress has been made in reducing caste and class disparities, sustained efforts are needed to eliminate systemic discrimination fully. Future policies must prioritize equitable resource distribution, participatory governance, and cultural sensitization to achieve lasting social harmony. Novelty: This paper contributes to the discourse on Nepali social stratification by integrating historical analysis with contemporary policy assessments. It highlights the dialectical relationship between power, class, and social change, offering a nuanced understanding of how metaphysical constructs influence societal transformation.